Diagnostic Performance of a Novel CXCL10 mRNA Release Assay for Mycobacterium tuberculosis Infection - Pan, Liping; Huang, Mailing; Jia, Hongyan; Deng, Guofang; Chen, Yu; Wei, Rongrong; Zhang, Mingxia; Li, Xin; Sun, Qi; Fang, Mutong; Ren, Pengfei; Xing, Aiying; et al. (Frontiers in Microbiology, 2022)
One-fourth of the world’s population has been infected with Mycobacterium tuberculosis (M.tb). Although interferon-gamma release assays (IGRAs) have been shown to be valid methods for identifying M.tb infection and auxiliary methods for diagnosis of active tuberculosis (TB), lower sensitivity and higher indeterminate rate were often detected among immunosuppressed patients. IP-10 was an alternative biomarker due to the higher expression level after M.tb antigen stimulation, but whether CXCL10 mRNA (the gene that transcribes for the IP-10 protein) can be used as a target for M.tb infection diagnosis was limited. Therefore, we aimed to evaluate the performance of a novel M.tb specific CXCL10 mRNA release assay in diagnosis of M.tb infection. Suspected TB patients and healthy controls were prospectively recruited between Mar 2018 and Nov 2019 from three hospitals in China. CXCL10 mRNA release assay and traditional interferon-gamma release assay (T-SPOT.TB) were simultaneously performed on peripheral blood. Of the 1479 participants enrolled in the study, 352 patients with definite TB and 153 healthy controls were analyzed. CXCL10 mRNA release assay provided a sensitivity of 93.9% (95%CI = 90.8% ‒ 96.2%) and a specificity of 98.0% (95%CI = 94.3% ‒ 99.6%) in diagnosis of M.tb infection, respectively; while T-SPOT.TB gave a sensitivity of 94.5% (95%CI = 91.5% ‒ 96.6%) and a specificity of 100% (95%CI = 97.6% ‒ 100.0%) in diagnosis of M.tb infection, respectively. The diagnostic performance of CXCL10 mRNA release assay was consistent with T-SPOT.TB, with a total coincidence rate of 95.0% (95%CI = 93.0% ‒ 96.9%) and a Cohen's kappa value of 0.89 (0.84 ‒ 0.93, P < 0.001). However, among TB patients with HIV co-infection (n = 14), CXCL10 mRNA release assay presented significantly higher positive rate [92.9% (66.1% ‒ 99.8%) vs. 61.5% (31.6% ‒ 86.1%), P = 0.029] than those of T-SPOT.TB. These results suggested that M.tb specific CXCL10 mRNA was a novel and useful target in diagnosis of M.tb infection.